The Effects Of Gamma Irradiation On Microbiological Safety, Biological Activities And Gallic Acid Content Of Euodia Malayana, Gnetum Gnemon And Khaya Senegalensis - Khawory, Muhammad Hidhir (2018)
Medicinal plants such as herbs and spices are often contaminated with high levels of bacteria, fungus and yeasts. Therefore, medicinal plants can be decontaminated using gamma irradiation to sterilize the microorganisms effectively. The aim of this study is to evaluate the effects of gamma radiation treatment on three medicinal plants, namely Euodia malayana, Gnetum gnemon and Khaya senegalensis at two different forms; methanol leaf extracts and dried leaves respectively. The microbial limit test studies indicated the suitable dosage of minimum and maximum gamma irradiation was 6-12 kGy for leaf extracts and 9-13 kGy for dried leaves of all the medicinal plants.